Tufted Puffin (Fratercula cirrhata) 3dRADseq and msat data ... - Burg, Theresa; Graham, Brendan (Borealis, 2024)
Abstract The tufted puffin ( Fratercula cirrhata ) is a medium sized seabird found throughout the North Pacific Ocean. Although populations of tufted puffins appear to be stable or increasing in some parts of their distribution, they are experiencing significant declines in other parts of their distribution, including in the Gulf of Alaska. Assessments of tufted puffin population status in Alaska are currently limited because little is known about population genetic structure. Similarly, there is little information on the amount of dispersal between populations in Alaska, and between populations in Alaska and those in the southern portion of the species’ range. If genetic analyses reveal significant genetic differentiation between tufted puffins nesting in different regions of Alaska, or evidence of local adaptation, then the apparent decline in the Gulf of Alaska becomes more of a conservation concern. There is general consensus within the tufted puffin research and management community that a study of ... : Methods We isolated high quality genomic DNA from 75 egg, feather, tissue, and blood samples using a salt extraction (Aljanabi and Martinez 1997). Samples were sent off to Université Laval where DNA was digested with three restriction enzymes PstI , NsiI , MspI and a library was prepared. Sequencing was done at Génome Québec at McGill University on a NovaSeq6000 S4 PE100. ...